The informal sector in Mexico, a burden or an engine for economic growth? - García Ortiz, Diego (Revista Internacional de Salarios Dignos, 2024)
Labor informality in Mexico is an economic phenomenon that affects both the productive structure and the social welfare of the country. The informal unemployment rate reaches 54.6% of the employed population; this sector is presented as a refuge for those who cannot access formal employment, but at the same time represents a challenge for sustainable economic growth. Although the informal sector contributes to absorb fluctuations in the labor market, its presence limits productivity, reduces tax collection and generates imbalances in access to social security and other public services. This paper seeks to quantify the impact of the informal sector on Mexico’s Gross Domestic Product (GDP), through a linear regression between the number of people employed in informality and GDP in millions of pesos and to reflect on whether informality is an obstacle to overcome or a temporary engine for the Mexican economy.